Implementasi Sistem Informasi Administrasi Kependudukan dalam Pengurusan Kartu Tanda Penduduk Elektronik - Jon Fredi Purba; Usman Tarigan; Irwan Nasution; Agung Suharyanto (PERSPEKTIF, 2019)
This research has been deceived by the importance of implementation of a of a government policy on the residency administrative information system (SIAK) about handling KTP-El has succeeded or did not succceed by reviewing the implementation of government policy which is based on the law of Indonesian RI country Number 24 in 2013 about The Administration of Residency. This study is meant to know how SIAK is implementation in the handling KTP-El and to find out what constraints are in the process. The methods are used in this research’s qualitative methods with the descriptive approach. The data collecting technique  was  carried  out  in  this  research  through  two  ways,  among  others  through secondary data (books, scientific papers, documents/archives) and obtained from field, observation and interview). From the research result it can be seen that the implementation of SIAK about the management of KTP-El has not been maximal, because there are still some obstacles and not yet have Special Regulation in the district office of Medan Baru Medan city, so there is still much need to be addressed. It is reviewed from 4 models of policy implementation according to Edward III, ie communication, disposition/attitude, resources, and bureaucratic structure. In this study, researchers also gain a new understanding that in the implementation of SIAK on the management of KTP-El good state service but it would be good apparatus not only run the activities of population administration, but also need to pay attention and care to public needs.